Leader-Member Exchange Theory in Healthcare: Examining Its Role in Enhancing Team Collaboration and Productivity - Velanganni , Dr.R.; Selvaraj , Dr. Vijayakanthan; Karpagham , Dr.C.; Ghate , Dr. AtulDattatraya; Saini , Dr. Rajvir (International Journal of Accounting and Economics Studies, 2025)
Leader-Member Exchange (LMX) Theory plays a crucial role in shaping leadership dynamics within healthcare settings by emphasizing the quality of relationships between leaders and their team members. Strong healthcare leadership is essential for promoting teamwork, boosting team unity, and increasing overall efficiency. This research investigates the use of LMX Theory within healthcare, exploring its influence on team effectiveness, employee involvement, and organizational productivity. A mixed-method approach is used, combining quantitative surveys with qualitative interviews of health workers to evaluate the effectiveness of LMX-manual leadership. Results indicate that a positive LMX relationship improves communication and increases job satisfaction and decision-making within medical teams. The study also addresses challenges related to LMX leadership, such as bias and vague roles. This conclusion concludes with strategic suggestions for health organizations to strengthen the leader-reinforcement relations and increase the team's productivity based on LMX principles.